The The Influence Of Return On Assets (ROA) And Capital Adequacy Ratio (CAR) On Profit Growth In The Banking Sector Listed On The Indonesia Stock Exchange For The Period 2021 – 2023 - Agnessia Ketaren; Jessi Charina Sembiring; Mutia Fitri Chania (Management Studies and Entrepreneurship Journal (MSEJ), 2025)
This study aims to examine the influence of Return on Assets (ROA) and Capital Adequacy Ratio (CAR) on profit growth using a descriptive quantitative approach with an explanatory research design. The population includes all companies in the sector listed on the Indonesia Stock Exchange (IDX) for the period 2021–2023, with 33 companies selected as samples through purposive sampling, resulting in a total of 99 observations. The data analysis process applies multiple linear regression. The F-test results confirm a significant simultaneous effect of ROA and CAR on profit growth (F count 21.949; p < 0.05). The t-test shows a negative and significant partial effect from both variables. The coefficient of determination (Adjusted R²) of 0.456 indicates that 45.6% of the variation in profit growth can be explained by ROA and CAR, while the remaining variation is influenced by other factors not included in this study.